2023
DOI: 10.1093/nar/gkad297
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of protein structures, functions and interactions using the IntFOLD7, MultiFOLD and ModFOLDdock servers

Abstract: The IntFOLD server based at the University of Reading has been a leading method over the past decade in providing free access to accurate prediction of protein structures and functions. In a post-AlphaFold2 world, accurate models of tertiary structures are widely available for even more protein targets, so there has been a refocus in the prediction community towards the accurate modelling of protein-ligand interactions as well as modelling quaternary structure assemblies. In this paper, we describe the latest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Structure of ClC3 and the functional ClC3 knockout were calculated from sequences as pdb (Protein Data Bank) files using IntFOLD7 ( McGuffin et al, 2023 ). From these structures, mages were produced using the pdb imaging program https://www.rcsb.org/3d-view with the region knocked out indicated (see Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Structure of ClC3 and the functional ClC3 knockout were calculated from sequences as pdb (Protein Data Bank) files using IntFOLD7 ( McGuffin et al, 2023 ). From these structures, mages were produced using the pdb imaging program https://www.rcsb.org/3d-view with the region knocked out indicated (see Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Three of them used AI-based predictions: AF2 for subunit modeling, AF2 for subunit and subcomplex modeling, and AF2 and RF for subunit and subcomplex modeling . By the end of 2022, the CASP15 competition highlighted the efficiency of ML approaches for the structural determination of protein assemblies. , While the need for MSAs on both partners appears to be a limitation of AF2 when attempting to predict protein interactions, strategies have been proposed to overcome it. On the one hand, it has been shown that MSA can be denoised .…”
Section: Predicting Oligomeric Modelsmentioning
confidence: 99%
“…Protein tertiary structures were modelled using AlphaFold2 (59) via the ColabFold v1.5.2-patch (60) or the AlphaFold patch of ChimeraX. Mutimeric structures were modelled by MultiFOLD (61) or AlphaFold2 and validated by ModFOLDdock (62). Structure similarity searches was done using Phyre2 (63) or FoldSeek (64).…”
Section: Protein Structure Prediction Protein Similarity Searches And...mentioning
confidence: 99%